A nano-based thermotherapy for cancer stem cell-targeted therapy. Issue 18 (2nd April 2020) - Suo, Xiaomin; Zhang, Juncai; Zhang, Yue; Liang, Xing-Jie; Zhang, Jinchao; Liu, Dandan
Abstract : Cancer stem cells (CSCs) exhibit high resistance to conventional therapy and are responsible for cancer metastasis and tumor relapse. Abstract : Cancer stem cells (CSCs) exhibit high resistance to conventional therapy and are responsible for cancer metastasis and tumor relapse. Therefore, it is of significance to develop effective novel strategies to target CSCs for cancer therapies. The challenges associated with developing novel strategies include specific CSC targeting and overcoming their therapeutic resistance. In the present review, we summarize the various strategies for CSC-targeted cancer thermotherapy and combinational therapy, and the potential challenges and prospects for future work in this emerging field.